2020
DOI: 10.1002/art.41311
|View full text |Cite
|
Sign up to set email alerts
|

Altered Lymphatic Vessel Anatomy and Markedly Diminished Lymph Clearance in Affected Hands of Patients With Active Rheumatoid Arthritis

Abstract: Objective To assess differences between lymphatic function in the affected hands of rheumatoid arthritis (RA) patients with active synovitis and that of healthy controls, using indocyanine green (ICG) dye and near‐infrared (NIR) imaging. Methods NIR imaging of the hands of 8 patients with active RA and 13 healthy controls was performed following web space injection of 0.1 ml of 100 μM ICG. The percentage of ICG retention in the web spaces was determined by NIR imaging at baseline and at 7 days (±1 day) after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…We have focused on the synovial lymphatic system during arthritic progression and flare (10,12,16,20,25,26,35,43,44), and the effects of interventions that specifically target lymphatic contractions, whose physiologic importance in supporting lymphatic drainage and subsequent onset of lymphedema have been established in preclinical and clinical studies (7,29,45,46). We have also performed transmission electron microscopy studies on WT, Expanding and Collapsed PLVs (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have focused on the synovial lymphatic system during arthritic progression and flare (10,12,16,20,25,26,35,43,44), and the effects of interventions that specifically target lymphatic contractions, whose physiologic importance in supporting lymphatic drainage and subsequent onset of lymphedema have been established in preclinical and clinical studies (7,29,45,46). We have also performed transmission electron microscopy studies on WT, Expanding and Collapsed PLVs (42).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we used CE-MRI to show that RA patients with the smallest change in lymph node volume during anti-TNF therapy experienced the greatest pain relief in symptomatic knee joints with a remarkably linear inverse correlation (28). Most recently, we utilized NIR-ICG imaging (10) to show that lymphatic drainage in the hands of RA patients with active disease is decreased compared to healthy controls (29). Furthermore, this reduced lymphatic drainage was associated with a decrease in the total length of ICG + lymphatic vessels on the dorsal surface of the hands, which continued to contract at a similar rate as controls (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the gold-standard clinical approach of lymphoscintography is effective for assessing lymphatic drainage in certain disorders, such as lymphedema, 16 it does not provide adequate resolution to monitor more subtle changes in CLV numbers and contractile function that have been noted by NIR-ICG imaging in both RA animal models and human subjects. 5, 6, 1-17, 28, 29 Thus, future work continuing to utilize and validate NIR-ICG imaging as a biomarker of lymphatic dysfunction has the potential to provide major advances in clinically screening and monitoring diseases with lymphatic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that lymphatic drainage in the hands of RA patients was reduced compared to that of healthy volunteers. 30 Interesting research on chronic inflammation including periodontitis also exists. For example, Hua Wang and colleagues demonstrated that there was impaired lymphatic flow in mice and patients with periodontitis.…”
Section: Lymphatic Flowmentioning
confidence: 99%